Protocols standardized for harvesting, preservation and valuation of ker fruits - Gurjar, P S; Samadia, D K; Kumawat, K L; Sarolia, D K (Indian Horticulture, 2025)
This study at ICAR–Central Institute for Arid Horticulture, Bikaner, Rajasthan, focused on ker or kair (Capparis decidua), an underutilized arid fruit of high nutritional and economic value. Traditional sun-drying practices reduce sensory and medicinal qualities, limiting commercialization. To address this, protocols for harvesting, acridity removal, preservation, and packaging were standardized. Innovative techniques, including lactic acid-based fermentation, brining, and freezing, were developed to retain fruit colour, quality, and phytochemical content, extending shelf-life up to 20 months. Market-oriented packaging technologies were also optimized. These interventions ensure year-round availability, enhance consumer acceptability, and promote livelihood security through sustainable, climate-resilient arid horticulture.